(untitled) (Research, Society and Development, 2024)
The sintering process is fundamental for the steel industry, as it contributes to reducing steel production costs. Furthermore, sintering also plays an important role in minimizing the environmental impact of the steel industry, as it allows the recycling of steel products and the reduction of the consumption of natural resources. The general objective of this study is to analyze the sintering process, verify the flaws that compromise production and implement improvements in the sintering process in a steel production company located in the south of the state, using the combination of statistical process control and the cycle PDCA (Plan-Do-Check-Act). Sintering faces several challenges, such as excessive porosity, poor densification, unwanted deformations, lack of uniformity in the chemical composition of sintered parts associated with a series of factors that contribute to significant losses in the process that cause negative balances when compared to control. statistical process, faced with such a problem, it was necessary to investigate the causes that caused losses in the process through the use of statistical control. The methodology used was the narrative review applied to a case study in a metallurgical company located in the south of RJ. As a result, several flaws were found that compromised the quality of the product and among many, the main one was the presence of new and inexperienced employees working in critical stages of the process. So, to solve the problem, the PDCA cycle was implemented, which showed positive results and increased the production balance by 3%.